A Pedagogy of Consilience and Renewal - Carolyn Calloway-Thomas (Central States Communication Association, 2022)
This essay calls for a pedagogy of consilience and renewal as a dynamic fusion of research and practices in order to provide a more coherent way of examining some of the keen, interlaced variables that trouble the academy and society. The project challenges scholars to study five key scholarship of learning variables that should help transform the way we look at pedagogy for the betterment of North American society and beyond. The variables-a quintile-are knowledge, geography, critical thinking, civic engagement, and empathy.